Vida y pensamiento internacionalista. Hernández Martín, Ramón, Madrid, Francisco de Vitoria, B.A.C., 381 págs - Hubeñak, Florencio (2004)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina; Argentina